PERSEPSI MASYARAKAT KABUPATEN WONOSOBO TERHADAP KEPEMIMPINAN ABDUL KHOLIQ ARIEF - septidina arsanti nugraheni; turtiantoro .; susilo utomo (Journal of Politic and Government Studies, 2016)
ABSTRACTRegent’ leadership in Wonosobo Regency is taking attention of Indonesian people broadly a lot. Being a Vice Regent collaborating with Trimawan Nugrohadi, Abdul Kholiq Arief then succeeded defeating his Regent in Pemilukada in Wonosobo Regency in 2005. It does not stop there, the next period in 2010, Abdul Kholiq Arief succeeded to maintain his position. His leadership stole many people’s attention by succeeding to get award as The Best Regent in 2012.Method that is used in this research is quantitative method. This is based on measuring society’s perceive towards Abdul Kholiq Arief’s leadership. Furthermore, this method is regarded exact because in this research, the researcher measured satisfaction level, and social effectiveness toward Abdul Kholiq Arief’s leadership.Abdul Kholiq Arief’s leadership that takes attention a lot of people out of Wonosobo Regency, in fact, it does not give the significat impact for broadly people. There are so many problems have been handled, however there are still problems felt by Wonosobo people. Matter of road infrastructure is still be a main problem left which have not handled yet. Some awards have been got by Abdul Kholiq Arief also do not change social prosperity generally.Keywords : Perceive, Leadership, Wonosobo.